Novel Bile Salt Stabilized Vesicles-Mediated Effective Topical Delivery of Diclofenac Sodium: A New Therapeutic Approach for Pain and Inflammation - Tamer M. Mahmoud; Mohamed M. Nafady; Hanan O. Farouk; Dina M. Mahmoud; Yasmin M. Ahmed; Randa Mohammed Zaki; Doaa S. Hamad (MDPI AG, 2022)
The oral delivery of diclofenac sodium (DNa), a non-steroidal analgesic, anti-inflammatory drug, is associated with various gastrointestinal side effects. The aim of the research was to appraise the potential of transdermal delivery of DNa using bilosomes as a vesicular carrier (BSVC) in inflamed paw edema. DNa-BSVCs were elaborated using a thin-film hydration technique and optimized using a 31.22 multilevel categoric design with Design Expert® software 10 software (Stat-Ease, Inc., Minneapolis, MI, USA). The effect of formulation variables on the physicochemical properties of BSVC, as well as the optimal formulation selection, was investigated. The BSVCs were evaluated for various parameters including entrapment efficiency (EE%), vesicle size (VS), zeta potential (ZP) and permeation studies. The optimized BSVC was characterized for in vitro release, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and incorporated into hydrogel base. The optimized DNa-BSVC gel effectiveness was assessed in vivo using carrageenan-induced paw edema animal model via cyclooxygenase 2 (COX-2), interleukin 6 (IL-6), Hemooxygenase 1 (HO-1) and nuclear factor-erythroid factor2-related factor 2 (Nfr-2) that potentiate anti-inflammatory and anti-oxidant activity coupled with histopathological investigation. The resulting vesicles presented VS from 120.4 ± 0.65 to 780.4 ± 0.99 nm, EE% from 61.7 ± 3.44 to 93.2 ± 2.21%, ZP from −23.8 ± 2.65 to −82.1 ± 12.63 mV and permeation from 582.9 ± 32.14 to 1350.2 ± 45.41 µg/cm2. The optimized BSVCs were nano-scaled spherical vesicles with non-overlapped bands of their constituents in the FTIR. Optimized formulation has superior skin permeability ex vivo approximately 2.5 times greater than DNa solution. Furthermore, histological investigation discovered that the formed BSVC had no skin irritating properties. It was found that DNa-BSVC gel suppressed changes in oxidative inflammatory mediators (COX-2), IL-6 and consequently enhanced Nrf2 and HO-1 levels. Moreover, reduction of percent of paw edema by about three-folds confirmed histopathological alterations. The results revealed that the optimized DNa-BSVC could be a promising transdermal drug delivery system to boost anti-inflammatory efficacy of DNa by enhancing the skin permeation of DNa and suppressing the inflammation of rat paw edema.